A Discrete Model of the Expected Loss for Catastrophe Insurance in Natural Disasters - Huang, Chongfu; Shi, Xing (Journal of Risk Analysis and Crisis Response, 2021)
The traditional actuarial model of catastrophe insurance is too theoretical. In many cases, it is of no avail. In this paper, we suggest a discrete model of catastrophe insurance to calculate the expected losses. We successfully applied to calculate the premium rate of the typhoon in Fujian Province, China. In this model, we use the conditional probability distribution of catastrophic events given a lower-catastrophe and the probability distribution of the catastrophe times to express randomness of catastrophe, use the matrix showing the damage ratio of a single insured object and the matrix showing the insurance loss to express the relationship between catastrophe and economic loss, and use the discrete probability distribution and catastrophe losses and above the relationship to calculate the expected loss. When we use the model to calculate the premium rate, we consider adjustment factors and insurance amount, and partly apply the general actuarial model. Research shows that the model versatility, easy operation, the results more reliable.